ДЛИТЕЛЬНАЯ ИММОБИЛИЗАЦИЯ - НЕИЗУЧЕННАЯ РЕАЛЬНОСТЬ. ЧАСТЬ 1 - А. Л. Вёрткин; В. А. Шевцова; А. А. Сокол (SINAPS LLC, 2012)
The article is dedicated to prolonged immobilization. Currently there is no common term, definition what is a prolongedimmobilization of patients, there is no tactic to manage such patients. We have tried to draw attention of the medical community to this problem - the results presented in the article are taken as an example of the hospital and clinics of Moscow.